FACTORS AFFECTING THE ROLE OF MOTHERS IN POSYANDU ACTIVITIES DURING THE COVID-19 PANDEMIC IN SEUNEUBOK ACEH VILLAGE PEUSANGAN DISTRICT BIREUEN REGENCY ACEH - Irma Fitria; Sri Raudhati; Ferri Zulfahmi (International Journal of Midwifery Research, 2022)
Posyandu (pos pelayanan terpadu) is the government's effort to facilitate the Indonesian people in obtaining maternal and child health services. The main goal of posyandu is to prevent an increase in maternal and infant mortality during pregnancy, childbirth, or afterward through community empowerment. The purpose of opening a posyandu during the pandemic is to become a reference for relevant stakeholders and service providers in implementing health efforts at Posyandu in adapting new habits. The purpose of this study was to determine the relationship between the factors that influence the role of mothers in posyandu activities during the pandemic. The design of this research is associative, namely the type of research that uses a cross sectional approach, the research instrument uses a questionnaire, and the sampling technique uses a total population method. The results of the education variable obtained a p value of 0.009 which means that there is a relationship between the level of education and the role of the mother in posyandu activities. From the age variable, a p value of 0.015 was obtained, meaning that there was a relationship between age and the role of the mother in posyandu activities. For the knowledge variable, a p value of 0.033 was obtained, meaning that there was a relationship between the knowledge factor and the mother's role in posyandu activities. Meanwhile, for the family support variable, a p value of 0.002 was obtained, meaning that there was a relationship between family support factors and the role of mothers in posyandu activities. It can be concluded that there is a relationship between education, age, knowledge, and family support factors with the role of mothers in posyandu activities during the COVID-19 pandemic.